Страхование: учебник / А. А. Гвозденко - Гвозденко Александр Андреевич (Проспект, 2004)
Прил.: с. 331-455 Экземпляры: СЭ (20071114) / Инвентарный номер: 1066580 / Цена: 300.00 / Сис.шифр: 65.9(2)26 / Авт.знак: Г 25 / ГРНТИ: 06.73.65 / ББК: 65.271я7